2009 International Conference on Telecommunications 2009
DOI: 10.1109/ictel.2009.5158656
|View full text |Cite
|
Sign up to set email alerts
|

Capacity of MIMO DSL systems using 100 MHz measured channel data

Abstract: This paper evaluates the capacity of MIMO DSL systems up to 100 MHz using short loops (50 and 200 meters) based on measured channel data. The experimental results show that these systems have capacities as high as 0.77 Gbps for the 50 m loop, for example.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Recent works described that this frequency values can achieve 100 MHz [2], [7], [14], even reaching 300 MHz, depending on the used cable quality [7]. Results of capacity simulations showed that this transmission channels can achieve near 1 Gb/s, and the use of DSM techniques to avoid crosstalk effects can help ensuring these data rates [2], [14], [15].…”
Section: Introductionmentioning
confidence: 93%
“…Recent works described that this frequency values can achieve 100 MHz [2], [7], [14], even reaching 300 MHz, depending on the used cable quality [7]. Results of capacity simulations showed that this transmission channels can achieve near 1 Gb/s, and the use of DSM techniques to avoid crosstalk effects can help ensuring these data rates [2], [14], [15].…”
Section: Introductionmentioning
confidence: 93%
“…A comparison between the fourth generation DSL proposal and older DSL generations, in terms of desirable data rates, transmission bandwidth and typical length of the used copper cable is illustrated in Figure 1. Some initial available works describing the research on the fourth generation broadband over copper can be find in (Acatauassu et al, 2009;Magesacher et al, 2006;Odling et al, 2009;van den Brink, 2010).…”
Section: State Of Art and Standardization Of The Fourth Generation Dslmentioning
confidence: 99%
“…Recent works described that this frequency values can achieve 100 MHz (Magesacher et al, 2006;Odling et al, 2009;van den Brink, 2010), even reaching 300 MHz, depending on the quality of the used cable (van den Brink, 2010). Results of capacity simulations showed that this transmission channels can achieve near 1 Gb/s, and the use of DSM techniques to avoid crosstalk effects can help ensuring these data rates (Acatauassu et al, 2009;Magesacher et al, 2006;Odling et al, 2009). It is important to notice that the use of FTTH does not necessary mean that fiber is deployed all the way to a point inside the home.…”
Section: Introductionmentioning
confidence: 96%
“…Recent works described that this frequency values can achieve 100 MHz (Magesacher et al, 2006;Odling et al, 2009;van den Brink, 2010), even reaching 300 MHz, depending on the quality of the used cable (van den Brink, 2010). Results of capacity simulations showed that this transmission channels can achieve near 1 Gb/s, and the use of DSM techniques to avoid crosstalk effects can help ensuring these data rates (Acatauassu et al, 2009;Magesacher et al, 2006;Odling et al, 2009).…”
Section: Introductionmentioning
confidence: 95%
“…Some initial available works describing the research on the fourth generation broadband over copper can be find in (Acatauassu et al, 2009;Magesacher et al, 2006;Odling et al, 2009;van den Brink, 2010 …”
Section: Introductionmentioning
confidence: 99%